GIS Suitability Analysis for Anaerobic Treatment Facility for Slaughter Houses in Anambra State of Nigeria - , E. C. Chukwuma; , G. O. Chukwuma; , L. C. Orakwe (Archives of Current Research International, 2016)
Investment in anaerobic digestion of bio-energy plants for slaughterhouse wastes is a good venture from environmental, economical and sustainable view point. Several researches have been undertaken in biogas potential of various substrates in Nigeria, there is need therefore to undertake further research on other factors such as site suitability analysis to achieve renewable energy target in the study area. Site selection which is a critical step in actualizing viable bio-energy was carried out in the study area using the power of Geographical Information System (GIS) technology. Several GIS thematic layers were obtained considering important factors in bio-energy plant location analysis. The various map layers were overlaid to obtain the final suitability map index with 4 classes which are the Most Suitable, Highly Suitable, Moderate Suitable and Not Suitable index. The result of the study reveals that the Most Suitable sites constitutes about 2.16% of all the study areas, Highly Suitable comprises of 34.25% of the study area, while Moderately Suitable sites forms 45.56% and Not Suitable composes of 18% of the study area respectively. Most of the Most Suitable sites were located in Onitsha North, Oyi and Idemili North Local Government Areas (L.G.A), few patches were seen in Orumba North, Idemili South, Orumba South, and Ekwusigo L.G.A.